Preliminary Adaptation of Motor Tests to Evaluate Fine Motor Skills Associated with Mathematical Skills in Preschoolers - Pedro Flores; Eduarda Coelho; Maria Isabel Mourão-Carvalhal; Pedro M. Forte (MDPI AG, 2023)
Mathematics is the subject in which many school-age children reveal difficulties. The literature has shown that fine motor skills, namely fine motor coordination and visuomotor integration, have been more robustly associated with mathematical performance. Studies have shown the importance that instruments have to evaluate these skills, however, the characteristics of these instruments do not fit the reality of kindergartens, they are usually time consuming and expensive and are usually administered by specialists. Thus, the main objective of this study was to identify, select, adapt and validate motor tests to evaluate fine motor skills associated with mathematical skills to allow the kindergarten teachers to apply them simultaneously to the class, with few material resources, in a short period of time and without the need for a lot of training to apply, score and classify. For this purpose, firstly, it was necessary to understand the main difficulties highlighted by kindergarten teachers regarding the use of instruments to evaluate fine motor skills and, thus, elaborate criteria to identify and select the tests that best fit the reality of kindergartens. The test identified, selected and adapted to evaluate fine motor coordination was threading beads from the Movement Evaluation Battery for Children, 2nd Edition. The main adaptation of the test was related to time, that is, instead of counting the time it takes the child to string the total number of cubes on the string, we counted the number of cubes the child strung on the string in a pre-defined time. To evaluate visual-motor integration, the test identified, selected and adapted was the Visual-Motor Integration (6th Edition) test. The main adaptation was related to material resources, that is, it will be possible to apply the test using only one sheet per child instead of the seven suggested by the original test. After the preliminary adaptation of the tests, their validation was performed by means of the degree of reliability (test-retest) and predictive validity. The results indicated that the adapted tests presented an excellent degree of reliability (>0.9) and could therefore be used to administer them simultaneously to the class group. The adapted Visual-Motor Integration test seems to be the most suitable one to be used by kindergarten teachers, in a classroom context, to simultaneously evaluate students' fine motor skills and associate their results with mathematical skills.